Does sharia compliance enhance ESG performance to better firm performance? - Arum Pujiastuti; Siti Abdillah Nurhidayah; Tri Joko Sulistiyanto (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2024)
This study investigates the influence of ESG and Sharia compliance on firm performance Current literature provides various findings explaining the effect of ESG on firm performance. The question arises as to whether compliance with Sharia, known for its ethical principles that share similar objectives with ESG, can enhance firm performance. This study introduces a novel approach by integrating the Sharia label to explore the relationship between ESG and firm performance, a topic not extensively covered in the literature, particularly in the context of Indonesia. This study employs a panel regression model with fixed effects using data from 235 firm-year observations of non-financial firms to estimate the results. The findings indicate a negative impact of ESG on firm performance. However, this study did not confirm the influence of Sharia on firm performance. To alleviate negative effect of ESG, companies could prioritize more efficient and impactful ESG practices.